Beach house reunion - Monroe, Mary Alice (Monroe, Mary Alice. Beach house series., 2018)
"Continuing the saga of her bestselling Beach House series, Mary Alice Monroe weaves together a tale of the struggles and triumphs of the historic Rutledge family of Charleston, South Carolina. Beautifully wrought and rich with keen insight, this is an illuminating tale of continuance, resilience, and one family's enduring love"--